REKA JANA DI YAYASAN JANAHITA MANDALA UBUD DALAM FOTOGRAFI DOKUMENTER - Dewa Putu Gede Suryantara; I Made Saryana; Anis Raharjo (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
Reka Jana is one of the activity programs at the Janahita Mandala Ubud Foundation, which focuses on instilling local arts and culture in Reading and Writing Balinese script and learning Balinese language for children from an early age. With the development of science and technology, causing the existence of local arts and culture to experience a shift, for example, most children begin to follow the way of dressing and language of western culture. Therefore, the Reka Jana program is expected to be able to re-instill local arts and local culture in children through reading and writing activities in Balinese script which are intended for children aged 5 – junior high school students, as well as the performance of the Dolana Anak Dance which contains learning about the use of language. Bali which is intended for children aged 5-8 years. The purpose of this research is to introduce, provide insight, raise public awareness of Balinese art and culture, as well as to add insight to the author. While the benefits can increase knowledge, insight into art and culture, and can attract the interest of the younger generation and the community to preserve Balinese art and culture. In this study, the methods of observation, literature study/interviews, photo shoots, finishing were used, by producing 15 works of documentary photography. Meanwhile, to analyze the author's work using Edfat's Theory, as well as Aesthetics, in idetional and technical settings.